ETIKA BERMEDIA SOSIAL: MORALITAS GEN-Z DI DESA DASAN GERES, KECAMATAN LABUHAN HAJI, LOMBOK TIMUR - Selian, Nadia Milyani; Rizal, Ahmad Ashril (Jurnal Riset Mahasiswa Dakwah dan Komunikasi, 2024)
This study aims to understand the behavior and ethics of Generation Z (Gen Z) in Desa Dasan Geres, Labuhan Haji District, East Lombok, in using social media from the perspective of Islamic communication. Using a mixed-method approach and a case study design, the research examines how Islamic values are applied in Gen Z’s digital interactions. The sample was selected through purposive sampling, focusing on Gen Z individuals who are active social media users, particularly Facebook. The findings reveal that most respondents are aware of the importance of maintaining ethics on social media, with 89.7% of their communication displaying positive sentiments, while 10.3% show negative sentiments, often related to emotional or provocative topics. However, some respondents prioritize creating engaging content over considering its moral impact. Social pressure is identified as a key factor influencing their behavior, while the application of Islamic values in their digital interactions remains suboptimal. This study highlights the need for continuous education and guidance on social media ethics based on the principles of Islamic communication. The role of families, educators, and communities is crucial in helping Gen Z become wiser, more responsible, and ethical in their digital activities. Such efforts are expected to foster a healthier digital environment and promote positive interactions that contribute to improved social relationships.